Parenting Patterns Based on Character Education Against Early Childhood Discipline - Lesmana, Gusman; Deliati, Deliati (Indonesian Journal Education, 2022)
This study aims to determine the relationship between character-based parenting and child discipline. The population in this study were 70 people and a sample of 10 children and their parents. The research instrument is an observation sheet in the form of free questions. Data analysis concluded that: (1). The tendency of character-based parenting applied by people is very good with a presentation of 50% in the high category. (2). The tendency of child discipline shown by early childhood is sufficient with a presentation of 30% in the sufficient category. (3). There is a positive and significant relationship between character-based parenting styles on children's discipline with a connectedness coefficient of 42.9%.